PENGARUH MEDIA FUN CARD DALAM MENINGKATKAN MINAT BELAJAR QUR'AN HADITS DI MADRASAH TSANAWIYAH TAHFIDZUL QUR'AN AL-FATAH BOYOLALI - Ardhiansyah, Fatah; Nurhidayati, Indah; Widoyo, Agus Fatuh (STKIP Pesisir Selatan, 2025)
This study aims to examine the effect of using the Fun Card learning media on students' learning interest in the Qur’an-Hadits subject at MTs Tahfidzul Qur’an Al-Fatah, Sambi Subdistrict, Boyolali Regency, for the 2024/2025 academic year. The background of the study arises from the low learning interest of students in Qur’an-Hadits lessons, which are often delivered monotonously and lack engagement. Therefore, an engaging and motivational learning media is needed to involve students actively. This research employed a quantitative approach with an explanatory method. Data collection was carried out through questionnaires distributed to 75 student respondents. Validity and reliability tests were conducted using SPSS, followed by t-tests and the coefficient of determination analysis. The results indicated that the use of Fun Card media has a significant effect on students' learning interest, with a significance value of 0.001 (< 0.05). The coefficient of determination was 66.6%, meaning that over half of the variance in students' learning interest can be explained by the use of Fun Card media. The implication of this study is that teachers should adopt innovative and engaging learning media to improve the effectiveness of Islamic education, particularly in Qur’an-Hadits instruction. Fun Card media can serve as a strategic alternative to create an active, participatory, and enjoyable learning environment.